A Non-anthropocentrism Approach to Environmental Ethics: A Theological Worldview - Kemi Anthony Emina (dialektika kontemporer, 2022)
The discussion regarding non-anthropocentrism as the most amicable solution to the current environmental crisis will be incomplete if scholars fail to include the issue of restoring man’s lost spirituality. Due to the dominance of the concept of man’s conquest of nature (anthropocentrism), which has led to an unprecedented rate of scientific and technological development in an attempt to artificialize the natural environment, the spiritual connection between man and nature has been severed. Modern quantitative science’s lack of a metaphysical foundation is said to destroy the spiritual connection between man and nature. This paradoxical situation necessitates the revival of eco-spirituality, which echoes ancient religions such as Hinduism, Buddhism, Jainism, and others. The goal of this paper is to investigate a second-order method of combating environmental degradation. This “second order” within the preview of eco-spirituality and non-anthropocentricism includes ancient religions such as Hinduism, Buddhism, Jainism, Christianity, and Islam. Further, the “second order,” under the label of “anthropocentrism,” is opposed to scientism, materialism, individualism, and extinctionism. This work submits that the universal acceptance of the holistic worldview reflected in the ancient religions listed above will aid in the creation of a society free from man’s dominance and exploitation, allowing him to live in peace and harmony with nature. Individuals’ inner minds must be developed in order to effect a change in their attitude toward nature. This requires the cultivation of the ideas inherent in religions. This research is carried out with the philosophical methods of critical and context analysis.